Analysis of Factors Contributing to Low Demand for Health Insurance in Indonesia - Tumpak Benny Aurixon; Runggu Christine Saragih; Nurul Asri Baharsyah; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2025)
This study analyzes the demand for insurance products in Indonesia as developing countries remains relatively low despite the significant market potential. From an economic perspective, insurance is a method for reducing risk by transferring and combining the uncertainty of financial losses. Thus, insurance is a social tool that transfers personal risks to all members of a group by utilizing pooled funds to pay for losses incurred under agreed upon terms. The insurance business in Indonesia has recently grown rapidly, including the entry of foreign investors into insurance businesses, either through share ownership or majority ownership in national insurance companies, with the increasing need for risk protection in a dynamic socio-economic context, it is crucial to more comprehensively understand the factors that drive and hinder insurance demand in developing countries. This study aims to review existing literature that explores the factors influencing insurance demand in developing countries, including individual, social, economic, and institutional aspects. A systematic literature review method was employed to analyze scholarly articles published over the past two decades. The findings reveal that factors such as income, education level, trust in financial institutions, financial literacy, government regulations, and risk perception significantly influence individuals' decisions to purchase health insurance products. These findings provide insights for policymakers and insurance industry stakeholders to design strategies aimed at enhancing insurance literacy and penetration in developing countries. The study also identifies research gaps that could be addressed in future empirical investigations. Additionally, cultural factors and access to insurance in Indonesia services also play a crucial role.